العشوائيات بين التراث والمعاصرة وأثرها في المجتمع العراقي - الزيدي، أنس عصام إسماعيل (جامعة الانبار - كلية التربية للعلوم الإنسانية, 2019)
لا شك أن ظاهرة السكن العشوائي صارت تقلق المجتمع العراقي، وتؤرق الحكومات المتعاقبة في بلادنا، لاسيما وأن هذه الظاهرة في نمو متزايد، لذلك شرعت في كتابة بحثي هذا، وتناولت فيه مشكلة السكن العشوائي في بلدنا الحبيب منذ ظهورها في ثلاثينيات القرن الماضي وإلى الآن، وتناولت أهم أسباب ظهورها الاقتصادية والسياسية والأمنية والاجتماعية، ومن ثم تناولت مواصفات السكن العشوائي من كافة جوانبه العمرانية والصحية والاجتماعية والأخلاقية، ليخرج البحث بأهم الوسائل التي يمكن من خلالها القضاء أو التقليل من هذه المشكلة الخطيرة في مجتمعنا.
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad and his family and companions. There is no doubt that the phenomenon of random housing has become of concern to the Iraqi society, and it harasses the successive governments in our country. Therefore, I started writing this research, And I dealt with the problem of random housing in our beloved country since its appearance in the thirties of the last century and so far, and addressed the most important reasons for their appearance in the economic, political, security and social aspects, And then I dealt with the specifications of random housing from all its aspects: urban, health, social and moral. To come up with the most important means through which we could eliminate or reduce this serious problem in our society.
Keywords: العمارة العربية -- السكن العشوائي -- العراق